Studi Koefisien Drag Aerodinamika pada Model Ahmed Body Terbalik Berbasis Metode Numerik - Marga Yogatama; Ramon Trisno (Jurnal Teknik Mesin, 2018)
transportation is one segment that produced greenhouse gasses. Transportation produced 14% emission in the world and will continuously arise. Because of that, so many effort made to reduce the rises. One of them is to reduce fuel consumption. To reduced fuel consumption we need to reduced the drag aerodynamic effect. This experiment use ansys software modeling with reversed ahmed body car model. Simulation does at 30 km/h, 60 km/h and 100 km/h. from the simulation we can get the stream turbulency and the drag coefficient at 0.073.